Current Trends of Reproductive Immunology Practices in In Vitro fertilization (IVF) ‐ A First World Survey Using IVF‐Worldwide.com. (8th August 2012) - Kwak‐Kim, Joanne; Han, Ae Ra; Gilman‐Sachs, Alice; Fishel, Simon; Leong, Milton; Shoham, Zeev
<x xml:space="preserve">Abstract</x> Problem Reproductive immunology has evolved from basic research studies to clinical applications. In this study, we aim to investigate the actual application of reproductive immunology concepts and findings in clinical reproductive medicine such as recurrent pregnancy losses (RPL), repeated implantation failures (RIF), and failed in vitro fertilization (IVF) cycles. Method of Study A web‐based survey was performed on IVF-Worldwide.com. Collected data were analyzed by the computerized software. Results A significant proportion of physicians recommend thrombophilia workups (86%), parental genetic study (79%), and immunologic evaluations (69%) to IVF candidates who have a history of RPL or chemical pregnancy losses. IVF physicians consider an immunologic workup when patients have two (30%) or three (21%) failed IVF cycles. Assays for anticardiolipin antibody, lupus anticoagulant, thyroid peroxidase antibody, and antinuclear antibody are the four most commonly ordered immunologic tests for RPL (88, 84, 50, 47% each) and RIF (68, 63, 38, 38% each). Cellular immune evaluations, such as NK assay, human leukocyte antigen study, Th1/Th2 study or immunophenotype assay, are less commonly ordered. Conclusions Reproductive immunology principles have been applied to the clinical management of RPL, RIF, and failed IVF cycles, and a significant proportion of IVF physicians acknowledge the importance of immunologic alterations with reproductive outcomes.